The Bologna Process and Learner Autonomy: Russian Specifics - M. A. Ivanova (Высшее образование в России)
The article deals with one of the problems that Russian higher education faces in the process of introducing credit-modular system as the implementation of one of the principles of Bologna  Declaration. It is the problem of insufficient learner autonomy demonstrated by many Russian freshmen, which prevents them from being real subjects of their learning in general and of student-centered learning in particular. The author believes that the causes of this problem should be searched both in the specific features of the national way of thinking and in the peculiarities of the Russian traditional schooling. As the result of the research done, the author comes to the conclusion that the majority of Russian freshmen are not ready to study in the terms of credit-modular system because of the lack of necessary study skills and inability to work ndependently. Hence, the designers of new State educational standards of both secondary and higher education should focus their attention on the process of learner autonomy development